2023
DOI: 10.2147/opth.s404369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of a Non-Diffractive Extended Depth-of-Focus IOL in Eyes with Mild Glaucoma

Abstract: Purpose To evaluate the clinical outcomes of a non-diffractive, wavefront-shaping extended depth-of-focus (EDOF) intraocular lens (IOL) in eyes with mild open-angle glaucoma (OAG). Setting Private practice; Sioux Falls, South Dakota. Design Prospective, open-label, interventional study. Methods In total, 52 eyes of 26 patients with mild OAG were enrolled and completed the study. All patients were bilaterally implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Full-text assessment was performed on the remaining 13 records; 2 were not retrieved, and 1 additional study was included from citation searching ( Figure 1 ). Twelve studies [ 22 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] fulfilled the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full-text assessment was performed on the remaining 13 records; 2 were not retrieved, and 1 additional study was included from citation searching ( Figure 1 ). Twelve studies [ 22 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] fulfilled the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies originated from the USA, four studies from Japan, three studies from Spain, one study from Australia, and one study from the UK. Three studies [ 40 , 41 , 49 , 50 ] reported on EDOF IOL outcomes, six studies [ 22 , 42 , 44 , 45 , 46 , 47 ] reported on toric IOL outcomes, one study [ 48 ] reported on MFIOL outcomes, and one study [ 43 ] reported outcomes from EDOF, bifocal, and trifocal IOL implantation. Study characteristics (author, publication year, sample size, age range, IOL type, surgery type, and outcomes) were extracted and summarized in Tables S2–S4 (Supplementary Material) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that patients with glaucoma may experience decreased CS after bifocal IOL implantation [ 7 , 9 , 11 ]. However, in a prior study, a non-diffractive, wavefront-shaping extended depth-of-focus (EDOF) IOL provided good visual acuity and high patient satisfaction in eyes with mild, pre-perimetric open-angle glaucoma (OAG) [ 12 ]. In addition, EDOF IOLs have been reported to provide similar CS and VF outcomes to those of standard monofocal IOLs in cataract patients without ocular comorbidities [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%